On the syntax and semantics of Spanish spatial prepositions - Ursini, Francesco-Alessio (Borealis – An International Journal of Hispanic Linguistics, 2013)
The goal of this paper is to offer a novel account on the Syntax and Semantics of Spanish Spatial Prepositions. This account is novel in at least three aspects. First, the account offers a unified syntactic analysis that covers understudied types of Spanish Spatial Prepositions (e.g. en el centro de, junto y a la izquierda de). Second, the account shows that such treatment can be extended to morphological phenomena, and can capture both their internal structure (e.g. de-bajo), and licensing patterns pertaining to argument demotion. The account also captures an alternation between "a-" (e.g. alante) and "de-" Prepositions (e.g. debajo), with respect to demotion, and is consistent with standard treatments of where-questions (dónde, in Spanish). Third, the account offers a "direct compositionality" semantic treatment, in which the interpretation of Spanish Spatial Prepositions is directly "read off" from their structure. This account is shown to capture all the semantic data discussed in the paper (argument demotion, interaction of Prepositions with Verbs, coordinated Prepositions), and to successfully extend previous accounts of this category.